Pengaruh Perputaran Kas Perputaran Piutang dan Likuiditas Terhadap Rentabilitas Ekonomi - Hupriah Futri; Mellya Embun Baining; Atar Satria Fikri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of cash turnover, accounts receivable turnover and liquidity, economic profitability. This study uses a quantitative approach with secondary data in the form of data obtained from informants and archives through a book of accountability reports for the management of the Sangkilan Mandiri Agro Cooperative, Terusan Village, Batanghari Regency, namely 2021-2022. The results of this study indicate that cash turnover and accounts receivable turnover do not affect economic profitability. Liquidity affects economic profitability. By using the F test simultaneously, cash turnover, accounts receivable turnover and liquidity have a joint effect on economic profitability. In this study, statistical calculations were used to analyze classical assumption tests including: normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, while hypothesis testing included: coefficient of determination T test and F test. This research method uses a quantitative approach